PERKEMBANGAN WATAK TOKOH UTAMA DALAM NASKAH DRAMA BALIATN KARYA AKHMAD BENYAMIN - Ningsih, Oktaviani Verawati; Nadeak, Parlindungan; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to increase the reader's understanding of the character development of the main character in Akhmad Benyamin's Baliatn drama script. The theory used in this study is the theory of behaviorism from B.F Skinner. This study uses a descriptive method, with a qualitative research form. The data source for this study is the Baliatn drama script by Akhmad Benyamin. The data collection technique used is the documentation technique. The data in this study are the dialogues of the characters in the form of quotations of words, phrases and sentences which show the development of the main character's character and the factors that influence it. KD 3.18 embarrassing the storyline, act by act, and conflict in the drama that is read or watched and 4.18 Shows one of the characters in the drama that is read or watched orally. Indicator 3.18.1 Identify scenes and conflicts in the Baliatn drama script by Akhmad Benyamin that is read. 3.18.2 Explaining the stages and conflicts in the Baliatn drama script by Akhmad Benyamin that is read. 3.18.3 Analyzing the scenes and conflicts in the Baliatn drama script by Akhmad Benyamin that is read. 3.18.4 Analyzing the character of the main character in the Baliatn drama script by Akhmad Benyamin and 4.18.1 Playing the role of one of the characters in the Baliatn drama script by Akhmad Benyamin being read and 4.18.1 Playing the role of one of the characters in the drama script which is read in accordance with the character's character.